Protein tyrosine phosphatase PTPN22 regulates IL‐1β dependent Th17 responses by modulating dectin‐1 signaling in mice. Issue 2 (20th October 2017) - Purvis, Harriet A; Clarke, Fiona; Jordan, Christine K; Blanco, Cristina Sanchez; Cornish, Georgina H; Dai, Xuezhi; Rawlings, David J; Zamoyska, Rose; Cope, Andrew P
Abstract: A single nucleotide polymorphism within the PTPN22 gene is a strong genetic risk factor predisposing to the development of multiple autoimmune diseases. PTPN22 regulates Syk and Src family kinases downstream of immuno‐receptors. Fungal β‐glucan receptor dectin‐1 signals via Syk, and dectin‐1 stimulation induces arthritis in mouse models. We investigated whether PTPN22 regulates dectin‐1 dependent immune responses. Bone marrow derived dendritic cells (BMDCs) generated from C57BL/6 wild type (WT) and Ptpn22 −/− mutant mice, were pulsed with OVA323‐339 and the dectin‐1 agonist curdlan and co‐cultured in vitro with OT‐II T‐cells or adoptively transferred into OT‐II mice, and T‐cell responses were determined by immunoassay. Dectin‐1 activated Ptpn22 −/− BMDCs enhanced T‐cell secretion of IL‐17 in vitro and in vivo in an IL‐1β dependent manner. Immunoblotting revealed that compared to WT, dectin‐1 activated Ptpn22 −/− BMDCs displayed enhanced Syk and Erk phosphorylation. Dectin‐1 activation of BMDCs expressing Ptpn22 R619W (the mouse orthologue of human PTPN22 R620W ) also resulted in increased IL‐1β secretion and T‐cell dependent IL‐17 responses, indicating that in the context of dectin‐1 Ptpn22 R619W operates as a loss‐of‐function variant. These findings highlight PTPN22 as a novel regulator of dectin‐1 signals, providing a link between genetically conferred perturbations of innate receptor signaling and the risk of autoimmune disease. Abstract : In response to dectin‐1 agonists Ptpn22 −/‐ or Ptpn22 R619W (orthologue of the human autoimmune associated variant) bone marrow derived dendritic cells (BMDCs) display enhanced Syk and Erk activation which correlates with increased IL‐1β secretion and leading to enhanced IL‐17 T‐cell responses. Findings highlight PTPN22 as a novel regulator of dectin‐1 signals.